Pituitary gland imaging - review of the literature - Dąbrowska, Izabela; Szydełko, Joanna; Wolski, Andrzej (Journal of Education, Health and Sport, 2021)
Introduction: is an endocrine gland located upon the hypophysial fossa of the sphenoid bone in the center of the middle cranial fossa and is surrounded by a small bony cavity (sella turcica). Radiological procedures are playing essential role in present diagnostic of pituitary gland. Pituitary tumours can now be visualized more accurately due to continued improvements in magnetic resonance imaging (MRI) techniques with gadolinium enhancement. Aim of the study: This article summarizes the current knowledge about radiological imaging of pituitary gland and in particular MRI scan procedures. In this paper we also want to show how the imaging of the pituitary gland looked like in the past and nowadays. Description of knowledge: Diagnostic procedures play primary role in present diagnosis and treatment of pituitary gland and sella turcica tumours. It is crucial for further diagnostic procedures to locate the tumour its size and margins. Currently magnetic resonance imaging is the more important examination just after the laboratory results. That modality easily shows exact location and tumours smaller than 1 cm. Radiological differentiation of lessions wouldn’t be possible without contrast agents. The latest MRI study protocols involve dynamic and delayed sequences for better visualisation and differential diagnostic. Conclusions: During the years radiological techniques evolved and gave us the perfect tool to visualize the pituitary gland and its pathologies.